The jewel hunter - Gooddie, Chris (WILDGuides, 2010)
A tale of one man's obsession with rainforest jewels, this is the story of an impossible dream: a quest to see every one of the world's most elusive avian gems--a group of birds known as pittas--in a single year. Insightful, compelling, and laugh-out-loud funny, this is more than a book about birds. It's a true story detailing the lengths to which a man will go to escape his midlife crisis. A travelogue with a difference, it follows a journey from the suburban straitjacket of High Wycombe to the steamy, leech-infested rainforests of remotest Asia, Africa, and Australia. Danger.